Fabrication of activated carbon electrode synthesized from sacred lotus leaf natural materials for supercapacitors - Ponken, Tanachai; Yaowanit, Kanoknan; Weluwanarak, Kanyaphat; Keacharoen, Apisit; Ponhan, Wichaid (Indochina Applied Sciences, 2022)
Supercapacitor has been the interesting issue in electric energy storage system. Supercapacitors carbon electrode was synthesized from a sacred lotus leaf. The none activated carbon sacred lotus leaf powder (CSLL) and the carbon sacred lotus leaf were mixed with potassium hydroxide (KOH) in the ratio of 1 : 1, 1 : 2, and 1 : 3 which were called CSLL, CSLL-1 : 1, CSLL-1 : 2 and CSLL-1 : 3, respectively. The structural, morphological properties and element component were analyzed with x-ray diffraction (XRD) technique, the field emission scanning electron microscope (FESEM) and energy dispersive x-ray spectroscopy (EDX), respectively. Electrical properties were measured by cyclic voltammetry (CV) and charge–discharge techniques. JCPDS 01-072-2091 data file confirmed the carbon-like (110) plan at 2 theta of 29.43° CSLL-1 : 1 and CSLL-1 : 2 showed high crystalline sizes. Morphology of CSLL-1 : 1 and CSLL-1 : 2 samples exhibited corrosion of surface clearly nevertheless carbon cluster adhered continuously on surface affect to higher the surface area. Carbon element of CSLL, CSLL-1 : 1 and CSLL-1 : 2 samples were obtained as high as of 74.50, 79.30 and 76 % by atomic, respectively which it was suitable characteristic of activated carbon electrode. The highest specific capacitance of CSLL-1 : 2 electrodes displayed approximately 40.85 F g-1 at the scan rate of 20 mVs-1. Moreover, the charge–discharge time of CSLL-1 : 1 and CSLL-1 : 2 electrodes showed the long discharge time more than the discharge time of CSLL-1 : 3 and CSLL electrodes. The performances of electrode demonstrated with charge-discharge of 1,500 and 1,000 cycles found that the CSLL-1 : 1 and CSLL-1 : 2 electrodes exhibited high stability. The suitable conditions ranges depicted between from the CSLL-1 : 1 to CSLL-1 : 2 ratios; furthermore, a sacred lotus leaf can fabricate the carbon electrode for supercapacitor.